2018
DOI: 10.1155/2018/2709654
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Stroke Risk Factors and Their Distribution Based on Stroke Subtypes in Gorgan: A Retrospective Hospital-Based Study—2015-2016

Abstract: Background Stroke is a leading cause of death and disability worldwide. According to the Iranian Ministry of Medical Health and Education, out of 100,000 stroke incidents in the country, 25,000 lead to death. Thus, identifying risk factors of stroke can help healthcare providers to establish prevention strategies. This study was conducted to investigate the prevalence of stroke risk factors and their distribution based on stroke subtypes in Sayad Shirazi Hospital, Gorgan, Northeastern Iran. Material and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
45
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 38 publications
16
45
2
4
Order By: Relevance
“…In the present study, total number of subjects in age group, ≥70 years, 60-69 ears, 50-59 years, 40-49 years and <40 years were 31%, 38%, 20%, 8% and 3% respectively. However, Mahdi Habibi-Koolaee et al 10 observed that most of the study subjects were aged more than 70 years and comprised of 43% of the study population. Population aged <40 years, 40-49 years, 50-59 years and 60-69 years comprised of 3.2%, 8.8%, 19.7% and 25.3% respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, total number of subjects in age group, ≥70 years, 60-69 ears, 50-59 years, 40-49 years and <40 years were 31%, 38%, 20%, 8% and 3% respectively. However, Mahdi Habibi-Koolaee et al 10 observed that most of the study subjects were aged more than 70 years and comprised of 43% of the study population. Population aged <40 years, 40-49 years, 50-59 years and 60-69 years comprised of 3.2%, 8.8%, 19.7% and 25.3% respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, 624 firstever strokes occurred in the study period and a crude annual incidence rate of first-ever stroke (FES) (139; 95% CI, 128-149) per 100 000 residents was seen. When this rate was adjusted for European people aged 45 to 84 years, it increased to 616 (95% CI, 567-664) for ischemic stroke, 94 (95% CI, 75-113) for intracerebral hemorrhage, and 12 (95% CI, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] for subarachnoid hemorrhage per 100,000. In the other hand, age-specific incidences in younger patients was higher than in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…There are large geographic variations in stroke incidence and mortality around the world. Most reported information about stroke incidence and prevalence in Iran has historically been based on stroke patients admitted in hospitals [4][5][6][7][8][9][10][11]. However, hospital-based studies usually cannot show real incidence and prevalence rates; population-based studies can report these more reliably.…”
Section: Introductionmentioning
confidence: 99%
“…9 Most common risk factors are hypertension, diabetes, alcohol, smoking and dyslipidemia among elderly stroke patients. [10][11] Since the incidence of stroke is increasing in our context, the study aims to identify various factors associated with stroke.…”
Section: Introductionmentioning
confidence: 99%